European yearbook of minority issues volume 8, 2009 (Martinus Nijhoff Publishers, 2011)
The European Yearbook of Minority Issues provides a critical and timely review of contemporary developments in minority-majority relations in Europe. It combines analysis, commentary and documentation in relation to conflict management, international legal developments and domestic legislation affecting minorities in Europe.